A Bibliometric Review on Readiness for Change and Organizational Change - Natalia, Vina; Ekowati, Dian (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This research aims to determine the development of readiness for change research trends both at the individual and organizational levels published in leading Scopus-based journals. The search process with the categories "title, abstract and keyword": "readiness AND change" in 2014-2023 found 7.988 articles, then using the keyword "organi*ation*" got 2.009 articles and with the keyword "employee" OR "individual" got 636 articles. In the subject areas of Social Sciences, Psychology, and Business, Management and Accounting, there were 255 final articles in English published. VOSviewer software is used to analyze the citation, and co-citation of articles extracted from the database. Research using the bibliometric method found that Mohamed Haffar wrote the most about dynamic capability. The institutions that publish the most papers related to readiness for change are Al-balqa Applied University, Salt, Jordan dan Business school, University of Birmingham, Birmingham, United Kingdom. Moreover, the country that publishes the most papers related to readiness for change is the United States. All keywords and the most widely used keywords by authors in journals with readiness for change dan organizational change in index